2001
DOI: 10.2337/diabetes.50.6.1282
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Extrapancreatic GLUT2-Dependent Glucose Sensors Control Glucagon Secretion

Abstract: GLUT2؊/؊ mice reexpressing GLUT1 or GLUT2 in their ␤-cells (RIPGLUT1 ؋ GLUT2 ؊/؊ or RIPGLUT2 ؋ GLUT2 ؊/؊ mice) have nearly normal glucose-stimulated insulin secretion but show high glucagonemia in the fed state. Because this suggested impaired control of glucagon secretion, we set out to directly evaluate the control of glucagonemia by variations in blood glucose concentrations. Using fasted RIPGLUT1 ؋ GLUT2 ؊/؊ mice, we showed that glucagonemia was no longer increased by hypoglycemic (2.5 mmol/l glucose) clam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 55 publications
1
55
1
1
Order By: Relevance
“…Whereas the ␤-cell model of glucose sensing would apply to the sensors controlled by high glucose, it is not clear how glucoprivation could stimulate feeding in a GLUT2-dependent manner. We previously reported that in ripglut1;glut2 Ϫ/Ϫ mice (in a mixed genetic background), the glucagon response to both hypoglycemic and hyperglycemic clamps was lost (46). We proposed that these results could be explained by the presence of two sets of glucose sensors, both GLUT2-dependent, one which stimulates glucagon production and which is progressively inhibited when glucose concentrations are increased and the other that generates an inhibitory signal for glucagon secretion, which increases when glucose concentrations rise.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the ␤-cell model of glucose sensing would apply to the sensors controlled by high glucose, it is not clear how glucoprivation could stimulate feeding in a GLUT2-dependent manner. We previously reported that in ripglut1;glut2 Ϫ/Ϫ mice (in a mixed genetic background), the glucagon response to both hypoglycemic and hyperglycemic clamps was lost (46). We proposed that these results could be explained by the presence of two sets of glucose sensors, both GLUT2-dependent, one which stimulates glucagon production and which is progressively inhibited when glucose concentrations are increased and the other that generates an inhibitory signal for glucagon secretion, which increases when glucose concentrations rise.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that insulin maintains an ongoing restraint on ␣-cell secretion and that loss of this inhibition by insulin may account for the hyperglucagonemia observed in insulin-deficient states. These initial observations were followed by a series of in vivo and in vitro experiments (23)(24)(25)(26)(27)(28)(29)(30) [AICAR]) and phlorizin. This combination induced moderate and equivalent hypoglycemia in both diabetic and nondiabetic animals in the absence of marked hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with inactivation of the Glut2 gene, and that express a transgenic glucose transporter in their pancreatic beta-cells to preserve normal glucose-stimulated insulin secretion (ripglut1;glut2 À/À mice), 61 display plasma glucagon levels in the fed state that are abnormally high. As glucagonemia can be rapidly normalized by ganglionic blockade, 62 this indicates that Glut2 (which is not expressed in alpha-cells) is required for the control of glucagon secretion. This was further shown by the lack of stimulation or decrease in plasma glucagon during, respectively, hypoglycemic or hyperinsulinemic clamp experiments.…”
Section: S64mentioning
confidence: 99%